Još jednom (posljednji put) o ljubavi - Kovač, Zvonko (Jezik in slovstvo, 2021)
The relationship and boundaries between the repeated renovations of modernism and the postmodern in the second half of the twentieth century are not easy to determine because they depend on innova tion based on originality and historical modernisms, and writing with or through (and in resistance to) tradition. My reading and understanding (analyses, interpretation) refers to comparative analyses of the poetry of Dane Zajc, Drago Ivanišević and Danijel Dragojević. Instead of a conclusion, there is a brief contrasting insight into the poetry of Tomaž Šalamun and Luko Paljetak, a poet of parallel neomodernism and postmodernism.
Keywords: 20. stoletje; 20th century; Croatian literature; Croatian poetry; Croatian poets; hrvaška književnost; hrvaška poezija; hrvaški pesniki; modernism; modernizem; postmodern; postmoderna; Slovenian literature; Slovenian poetry; Slovenian poets; slovenska književnost; slovenska poezija; slovenski pesniki